Sculpting leadership on employees' craft: The conceptual framework and measure of crafting leadership - Ferdinando Paolo Santarpia; Laura Borgogni; Giulia Cantonetti; Sara Brecciaroli (Administrative Sciences, 2025)
Organizations are questioning the effectiveness of one-size-fits-all leadership approaches in managing and developing employees. This article proposes that leaders can support employees in crafting their work experience. By integrating the behavioral domains conducive to job crafting, the Michelangelo model and the leadership for organizational adaptability framework, we introduce the crafting leadership model-a behavioral style where leaders adapt their behaviors to employees' characteristics to co-construct their fit at work and foster the development of both people and organizations-providing a conceptual foundation for identifying its key behavioral facets and highlighting its unique value compared to existing leadership styles. We developed and validated a questionnaire using structural equation modeling. In Study 1 (N = 2137) and Study 2 (N = 1507), the questionnaire was tested for factor structure, reliability, discriminant, and predictive validity. The results supported a higher-order structure of crafting leadership, underlying three distinct behavioral facets: tailoring, person-organization alignment, and catalyst. Results revealed that crafting leadership (a) was distinct from strength-based, servant, and transformational leadership and (b) correlated with and explained additional variance in employee outcomes, namely needs-supplies fit, meaningful work, job-crafting behaviors, work engagement, and turnover intentions. Implications for research and practice are discussed.
Keywords: 350; leadership behavior; crafting leadership; job crafting; needs-supplies fit; workengagement; meaningful work; turnover intentions; scale validation; Michelangelo model; organizational adaptability